Manifesto - National Alliance of Democratic Forces
001-0074-004 -2- The Spanish Democracy, the very first to spill its blood against Nazi madness, is in complete concord with the United Nations and is fully convinced that the triumph of Allied Arms, means the victory of democracy, of democracy as a whole and individual democracy in every country. With the same confidence the progressive Spanish Forces, hope with good reason, that victory will bring about the necesary objective conditions, of the moral and material order that will demand their access to power. The nefarious buffooneries of the ruling Falange will have no influence whatsoever in bringing this about. In their revisionist anxiety they have always made their tenets fit the case, according to military events and turned full circle their international policy. A famous editorial in their press organ "ARRIBA" stated not so long ago: "In order to win, the falangist must understand international events in their true light without attempting to deface them, keeping aware that on those facts and no others will be established the possible convivence for post-war". These facts are nothing more than the triumph of the United Nations. And in these clear and definite words is expressed the whole idea of the present Franco regime. Have the interior politics changed accordingly? Definitely not! The ferocious repression still continues witn the same satanic fury. The feudal despotism still has a hold on life and property. No one in Spain is safe, threats and terror hold sway. The Falange devotes most of its energy to terrorising the population. The whole of Spanish life, the whole administration amounts to little more than a gigantic racket. But the Falange and its methods have been unmasked. The farce is nearing its end. The days of terror and tyranny are numbered, National-sindicalism does not fool anybody any longer, sympathisers or otherwise. The political and trade union organisations which are behind the following manifesto -and they represent by far the greatest majority of popular forces in the country- believe that the time has come to solve the problems of the nation. And furthermore, they realise that there is one road and one road only leading to that solution, the road of democracy. Now, let it be made clear, that to shake off tyranny and start afresh with a regime of freedom, means: Firstly: To maintain on one hand the historic continuity of Republican Democracy. Secondly: To facilitate, on the other hand, the free decision of future political forms and their organic machinery. Moreover it urges with firm determination the reestablishment of much-trampled right and justice. For these very reasons the organisations forming the N.A. of D.F. -reserving everyone of them their full rights and individuality akin to their political ambitions and in consideration of the serious situation of the country- have reached a political pact of whose far-reaching consequences the Spaniards to whom we offer it will be able to pass judgment. BASIS OF THE AGREEMENT. First: To restore the Republican Order. Second: To form a democratic government that will take up all powers (as long as popular opinion is consulted by means of universal suffrage) with the support of the parties and organisations represented in it. Third: To maintain social and public discipline firmly and effectively, taken care conscientiously of its accomplishment. Fourth: Declaration on the validity of official by-laws. The surviving ones, in addition to the new ones will form the code on which the latter will base its administration. Fifth: Of special significance to this government will be restoration of the disturbed juridical order. So as not to detract from that end, the government will 292/946/1/75(ii)